2019
DOI: 10.1021/acs.analchem.8b04906
|View full text |Cite
|
Sign up to set email alerts
|

13C- and 15N-Isotope Analysis of Desphenylchloridazon by Liquid Chromatography–Isotope-Ratio Mass Spectrometry and Derivatization Gas Chromatography–Isotope-Ratio Mass Spectrometry

Abstract: Widespread application of herbicides impacts surface water and groundwater. Their metabolites (e.g., desphenylchloridzon from chloridazon) may be persistent and even more polar than the parent herbicide, which increases the risk of groundwater contamination. When parent herbicides are still applied, metabolites are constantly formed and may in addition be degraded. Evaluating their degradation based on concentration measurements is, therefore, difficult. This study presents compound-specific stable isotope ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 47 publications
3
35
0
Order By: Relevance
“…Additionally, this study confirmed that the application of CSIA in combination with solid-phase extraction 27,39 is feasible for the analysis of polar micropollutants in drainage water at environmentally relevant concentrations. Thus, it can be also applied to studies in agricultural soil and groundwater from common unconsolidated sand and/or gravel aquifers with catchment areas within agricultural production.…”
Section: Environmental Significance and Outlooksupporting
confidence: 72%
See 4 more Smart Citations
“…Additionally, this study confirmed that the application of CSIA in combination with solid-phase extraction 27,39 is feasible for the analysis of polar micropollutants in drainage water at environmentally relevant concentrations. Thus, it can be also applied to studies in agricultural soil and groundwater from common unconsolidated sand and/or gravel aquifers with catchment areas within agricultural production.…”
Section: Environmental Significance and Outlooksupporting
confidence: 72%
“…On the other hand, for both moraine and gravel soil, δ 15 N values of the DPC formed are, as hypothesized in Figure S1, close to the nitrogen isotope signature of the applied CLZ. Based on the findings of Lingens et al 20 , the pyridazinone-ring of the CLZ molecule is not involved in the first transformation steps (dioxygenation of the phenyl-ring, Figure S1) so that no significant nitrogen isotope fractionation is expected during CLZ transformation to DPC 27,29,48,49 . As the isotope effect during multi-step reactions is reflected by the rate-limiting steps, our results indicate that the amidase-driven cleavage of the moiety (2-hydroxymuconate) at the C-N bond, may be not ratelimiting.…”
Section: Andmentioning
confidence: 98%
See 3 more Smart Citations